PENGARUH PENGEMBANGAN KARIR DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA BADAN PENGAWAS PEMILU PROVINSI SULAWESI SELATAN - Darajatun, Azizah; Idris, Abdi Akbar; Kurniawan, Agung Widhi; Burhanuddin, Burhanuddin; Haeruddin, Ilham Wardhana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine how the influence of Career Development and Competence on the employee performance of the Badan Pengawas Pemilu Provinsi Sulawesi Selatan. The population in this study were employee of the Badan Pengawas Pemilu Provinsi Sulawesi Selatan and the sample used was 54 people using saturation sampling. Data was collected by using observation and questionnaire methods. The data analysis technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS). The results of this study indicate that simultaneously Career Development and Competence have a significant effect on Employee Performance. Partially, career development has a significant effect on employee performance and competence has a significant effect on employee performance.